Deteksi Dini Stunting Melalui Edukasi Orang Tua dan Pengukuran Antropometri Balita di Posyandu Pasir Putih Kelurahan Baurung - Hilky Ofan; Masyitah wahab; Jamila Kasim; Maryam Jamaluddin (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Stunting remains a major public health challenge in Indonesia, requiring systematic early detection and community-based interventions. This community service activity aimed to implement early stunting detection through parental health education and anthropometric measurements of children under five at Posyandu Pasir Putih, Kelurahan Baurung, Kecamatan Banggae Timur, Kabupaten Majene, West Sulawesi. A participatory approach was used, combining interactive health education sessions with standardized anthropometric screening (weight, height/length, mid-upper arm circumference, and head circumference) for 35 toddlers aged 0–59 months. Parental knowledge was assessed using pre-test and post-test questionnaires administered to 38 parents. Results showed a significant increase in parental knowledge, from a mean pre-test score of 52.4 (poor category) to 81.6 (good category) on post-test. Anthropometric assessment revealed that 13 out of 35 toddlers (37.1%) were identified as stunted (25.7% stunted; 11.4% severely stunted). All identified cases were referred to the local health center (Puskesmas) for specific nutritional interventions including supplementary feeding and intensive nutrition counseling. These findings indicate that integrated anthropometric screening combined with targeted parental education is an effective strategy for early stunting identification at the community level. Posyandu plays a crucial role as a platform for translating anthropometric data into meaningful risk communication and promoting sustained community engagement in child growth monitoring